Bacillus spp. Fermented Plant Protein Mix as a Potential Fishmeal Substitute in the Diet of Penaeus monodon: Emphasis on Nitrogen Metabolism. (13th July 2022) - Rajaram, Vanjiappan; Jannathulla, Rajabdeen; Rajendran, Rengasamy; Ambasankar, Kondusamy; Panigrahi, Akshaya; Dayal, Jagabattula Syama
Abstract : A feeding experiment (60 days) was conducted to evaluate the effect of Bacillus spp. fermented plant protein mix in Penaeus monodon . A control diet (CNT) contains 25% fishmeal, of which 50% was substituted (w/w) with Bacillus spp. fermented plant protein mix at two different concentrations of 0.25 and 0.50% (PP-0.25 and PP-0.50, respectively), while the diet prepared with untreated ingredients served as a negative control (PP-0). The daily growth coefficient (DGC) did not differ in the groups fed CNT, PP-0.25, and PP-0.50 diets. The feed conversion ratio (FCR) was low in the CNT and PP-0.50 diets, while (protein efficiency ratio (PER) and apparent protein utilization (APU) were high in the PP-0.50-fed group. The dietary change did not affect survival and whole-body composition, while free amino acids varied among the treatments. Increased nitrogen intake and oxygen consumption were observed in subadults fed with CNT diet. Increasing Bacillus spp. concentrations significantly lowered ammonia-N excretion by 2.09-11.69%. Regression analysis revealed higher coefficients for oxygen consumption (R 2 = 0.8625 ) and O : N ratio (R 2 = 0.7791 ), while it was 0.5894 for ammonia-N excretion. The dietary change significantly influenced hemolymph indices and chitinase, glutamate dehydrogenase (GDH), and arginase activity. Results conclude that Bacillus spp. fermented plant protein mix could be a viable fishmeal substitute in shrimp feed.